Hybrid supervisory control of the brine heater for multi stage flash desalination plants - Gambier, Adrián; Fertig, Matthias Wilhelm; Badreddin, Essameddin (IFAC Proceedings Volumes, 2016)
Multistage Flash desalination is the most common process large-scale distillation process to produce freshwater from seawater. Its operation is energy intensive and essential for the maintenance of life support in regions with scarcity of water resources. Such plants need an efficient control system in order to be economically viable. Fortunately, the plant can be broken down into subsystems, where the brine heater has the function to increment the brine temperature to the saturation value. Temperature control of the brine is crucial for the overall stability and economy of plant operation. Here, an adaptive control system based on PID controllers supervised by a hybrid automaton is proposed for the brine temperature control loop.
Elektronische Reproduktion der Druckausgabe
Gesehen am 14.01.2020